2017
DOI: 10.18632/oncotarget.19092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roniciclib in preclinical models of anaplastic thyroid cancer

Abstract: Many human cancers have altered cyclin-dependent kinase activity. Inhibition of cyclin-dependent kinases may arrest cell cycle progression and represents an important strategy in the treatment of malignancies. We evaluated the therapeutic effects of roniciclib, a cyclin-dependent kinase inhibitor, as a treatment for anaplastic thyroid cancer. Roniciclib inhibited anaplastic thyroid cancer cell proliferation in a dose-dependent manner. Roniciclib activated caspase-3 activity and induced apoptosis. Cell cycle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Our prior study revealed that roniciclib decreased survivin expression in anaplastic thyroid cancer tumors [ 28 ]. Survivin is a component of the chromosomal passenger complex that is involved in mitotic progression [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our prior study revealed that roniciclib decreased survivin expression in anaplastic thyroid cancer tumors [ 28 ]. Survivin is a component of the chromosomal passenger complex that is involved in mitotic progression [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three human ATC cell lines, 8505C, 8305C, and KAT18, were evaluated in this study 24‐26 . Cell line identity was validated using DNA short tandem repeat profiling and cells were stored in liquid nitrogen until use.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis has an important role in cancer therapy (Galluzzi et al 2012). Roniciclib activates caspase-3 activity and induces apoptosis in HeLa and anaplastic thyroid cancer cell lines (Siemeister et al 2012, Lin et al 2017a. Therefore, we evaluated the effects of roniciclib on apoptosis in papillary and follicular thyroid cancer cell lines.…”
Section: Roniciclib Induced Apoptosis In Wdtc Cell Linesmentioning
confidence: 99%
“…Roniciclib inhibits cell cycle transition, promotes caspase-3 activity and stimulates apoptosis in vitro. Oral administration of roniciclib has potent efficacy in impeding tumor growth of cervical, lung and anaplastic thyroid cancer xenografts, with favorable safety profiles in animal models (Siemeister et al 2012, Lin et al 2017a. The objective of this study was to evaluate the therapeutic effects of roniciclib in WDTC in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%